Consumers' reasons for purchasing low involvement goods by mail catalogue: Preliminary measurement guidelines - N. S. Terblanché; C. Boshoff; E. V.D.M. Smit (South African Journal of Business Management, 1999)
New forms and applications of technology have enabled business organisations to increasingly utilise multiple channels for the distribution of retail products. One example, mail-order catalogue buying, has now become an acceptable shopping format for larger numbers of consumers. Earlier research clearly indicated that non-shop shopping, such as buying by mail-order catalogue, is not only very different from shop shopping, but consumers also undertake non-shop shopping for distinct reasons. The primary objective of the research reported here was to identify the reasons underlying the purchasing of low involvement products by mail-order catalogue and to develop a reliable and valid instrument that could identify and measure such reasons.
Keywords: 650